2011
DOI: 10.1103/physreva.83.013608
|View full text |Cite
|
Sign up to set email alerts
|

Co-propagating Bose-Einstein condensates and electromagnetic radiation: Emission of mutually localized structures

Abstract: Using a semi-classical model to describe the interaction between coherent electromagnetic radiation and a Bose-Einstein condensate in the limit of zero temperature, including the back action of the atoms on the radiation, we have analyzed the phenomenon of emission of solitary-like wave packets which can accompany the formation of mutually localized atom-laser structures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…Soon after the formation of filaments one observes on-axis collapse in both fields as the focusing nonlinearities overwhelm the system dynamics, akin to the BEC collapse experimentally studied in [32]. Although outwith the scope of this letter, our model also confirms similar results seen in 1D [33] that show that on-axis collapse can be avoided when the amplitude of the BEC is significantly different to that of the optical field. In that case the dominant dynamics are linear rather than the highly nonlinear dynamics which we report here, with the optical field acting more as a potential on the BEC rather than a coupled field.…”
supporting
confidence: 85%
“…Soon after the formation of filaments one observes on-axis collapse in both fields as the focusing nonlinearities overwhelm the system dynamics, akin to the BEC collapse experimentally studied in [32]. Although outwith the scope of this letter, our model also confirms similar results seen in 1D [33] that show that on-axis collapse can be avoided when the amplitude of the BEC is significantly different to that of the optical field. In that case the dominant dynamics are linear rather than the highly nonlinear dynamics which we report here, with the optical field acting more as a potential on the BEC rather than a coupled field.…”
supporting
confidence: 85%
“…Soon after the formation of filaments one observes on-axis collapse in both fields as the focusing nonlinearities overwhelm the system dynamics, akin to the BEC collapse experimentally studied in [28]. Although outwith the scope of this letter, our model also confirms similar results seen in 1D [29] that show that on-axis collapse can be avoided when the amplitude of the BEC is significantly different to that of the optical field. In that case the dominant dynamics are linear rather than the highly nonlinear dynamics which we report here, with the optical field acting more as a potential on the BEC rather than a coupled field.…”
supporting
confidence: 85%
“…It is clear that if the two components are generated at a distance ∆x < ∆x 0 , the two solitons will repel each other and be ejected away whereas two components generated at ∆x > ∆x 0 will attract each other with the possible creation of a bound state where the two components oscillate about their equilibrium position. This model, based on the existence of multi-peaks solutions of our stationary equations, thus explains quite well the qualitative features of the numerical results of [7], both the jet emission and the formation of a bound state. It thus seems possible to say that the dipole-dipole interaction can lead to the generation of two-peak structures for both atoms and laser but the destiny of the two peaks is that of moving apart from each other in a solitary-like fashion or to move towards each other.…”
supporting
confidence: 76%
“…It has been shown via numerical simulation of the coupled dynamics that self-localised structures and mutual atom-light guiding can be achieved exploiting the dipole-dipole interactions, [6]. In particular it was observed that solitary-like localised structures can be generated and emitted from a central bunch of atoms, [7]. This is suggestive of analogous optical effects such as soliton ejection, see [8] and references therein, and we will try here to obtain an understanding of how the structures ejected in laser-BEC interactions are created and emitted.…”
mentioning
confidence: 99%
See 1 more Smart Citation